2021
DOI: 10.1155/2021/6696041
|View full text |Cite
|
Sign up to set email alerts
|

A Noninvasive Prediction Model for Hepatitis B Virus Disease in Patients with HIV: Based on the Population of Jiangsu, China

Abstract: Objective. To establish a machine learning model for identifying patients coinfected with hepatitis B virus (HBV) and human immunodeficiency virus (HIV) through two sexual transmission routes in Jiangsu, China. Methods. A total of 14197 HIV cases transmitted by homosexual and heterosexual routes were recruited. After data processing, 12469 cases (HIV and HBV, 1033; HIV, 11436) were left for further analysis, including 7849 cases with homosexual transmission and 4620 cases with heterosexual transmission. Univar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 41 publications
(47 reference statements)
0
7
0
Order By: Relevance
“…[17] However, Decision tree, Random forest, AdaBoost, XGBoost, and GRNN prediction techniques, described as machine-learning-based forecasting models, specialize in dealing with big data and nonlinear problems but require a large number of samples. [32] For example, Yin et al [32] used Decision tree, Random forest, AdaBoost, XGBoost, and GRNN prediction techniques to fit and predict patients co-infected with hepatitis B virus (HBV) and human immunodeficiency virus (HIV) in Jiangsu, China, which provided 12469 samples sizes in the study. Compared to GM (1, 1) and machine-learning-based forecasting models, the SARIMA model has numerous advantages for infectious disease prediction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[17] However, Decision tree, Random forest, AdaBoost, XGBoost, and GRNN prediction techniques, described as machine-learning-based forecasting models, specialize in dealing with big data and nonlinear problems but require a large number of samples. [32] For example, Yin et al [32] used Decision tree, Random forest, AdaBoost, XGBoost, and GRNN prediction techniques to fit and predict patients co-infected with hepatitis B virus (HBV) and human immunodeficiency virus (HIV) in Jiangsu, China, which provided 12469 samples sizes in the study. Compared to GM (1, 1) and machine-learning-based forecasting models, the SARIMA model has numerous advantages for infectious disease prediction.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that according to the data features of the study, choosing the right model is a prerequisite for exploring credible results. Based on a literature review and our previous research, we found that the ARIMA, [3] GM (1, 1) model, [3] Decision tree, [32] Random forest, [32] AdaBoost with decision tree (AdaBoost), [32] extreme gradient boosting decision tree (XGBoost), [32] Elman network, [33] and generalized regression neural network (GRNN) [34] can be used to predict hepatitis B. Among these, the GM (1,1) model is suitable for short-term prediction with small sample sizes [17] .…”
Section: Discussionmentioning
confidence: 99%
“…The purpose of the feature selection was to eliminate redundant and irrelevant variables. Potential features can be selected by traditional statistical methods ( 15 ). We applied the filter method of univariate logistic regression to choose the feature subsets in which the independent variables are correlated with the dependent variable in the original data structure.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have used logistic regression or Cox proportional hazards regression models to establish the prediction tool of HIV infection among MSM, but performance is not great due to the problems of data structure which are often non-linear, abnormal, and heterogeneous ( 11 14 ). Compared to the above traditional models, the machine learning algorithm provides a new method to construct models, since it can balance the deviation and variance of data ( 15 ). Nowadays, machine learning has been widely applied in the medical field, mainly reflected in medical auxiliary diagnosis and classification prediction, such as image-based cancer diagnostics ( 16 , 17 ).…”
Section: Introductionmentioning
confidence: 99%
“…Yashik et al [2]: Two machine learning methods were applied: SVM and neural network. Yin et al [3]: DT, RF, and AdaBoost with DT (AdaBoost) were applied. AdaBoost showed the highest accuracy = 92.8%, precision = 91.5%, recall = 94.4%, F − 1 = 93.0%, and AUC = 96%.…”
Section: Related Workmentioning
confidence: 99%